THE ATTIC SCOLIA AND THE ABUSE-LYRICS IN OLD COMEDY - McNamara, Patrick Shawn (My University, 1989)
The purpose of this thesis is to examine two elements of popular Attic culture as they appear in Old Comedy: the so-called Attic scolia, and the ritualized abuse often associated with cult, which takes the form of the abuse-lyrics so prominent in the iambic scenes. This will be done primarily through a reexamination of an old article by Ernst Wust [Philologus 77 (1921)]. This is necessary in that Wust's arguments seem to have been accepted as valid. It will be shown that, although there are Attic scolia present in Old Comedy (in different forms, e.g. in partial citations and in parody), they are not as pervasive and do not play as formative role in the structure of Old Comedy as Wust asserted. As for the abuse-lyrics, it will be shown that they derive from several traditions of invective: primarily from the cultic aιοxρoλoyιa and the good-natured abuse frequently associated with religious celebrations, especially those peculiar to women, but also from the Iambographers, whose influence is explicitly attested by the comic poets themselves. In addition, in both parts of this thesis the frequent use of forms of folk-poetry, and the significance of this, will be demonstrated.
Keywords: Classics; Classics